Atypical teratoid/rhabdoid tumor arising in a malignant glioma. Issue 1 (29th July 2016) - Bozzai, Barbara; Hasselblatt, Martin; Turányi, Eszter; Frühwald, Michael C.; Siebert, Reiner; Bens, Susanne; Schneppenheim, Reinhard; Kool, Marcel; Stelczer, Gábor; Hortobágyi, Tibor; Hauser, Peter
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT), a highly malignant brain tumor in young children, usually arises de novo and has only rarely been described as a secondary malignancy. Here, we present a case of a child with glioblastoma, who was treated postoperatively by a combination of temozolomide, irradiation, and bevacizumab. AT/RT was diagnosed as a secondary tumor, 2.5 years following primary diagnosis. The child died 13 months after the diagnosis of AT/RT. This case demonstrates that malignant gliomas may give rise to AT/RT. It also emphasizes the diagnostic value of a repeated tumor biopsy in the recurrence setting.